Pemanfaatan Carica untuk Meningkatkan Ekonomi Daerah melalui Produk Bernilai Tinggi - Fani Familia; Ahmad Tarikul Majid; Syafiq Dimas Perdana; Ainul Huda; Sri Jumini (CATHA SAINTIFICA, 2026)
The natural resource potential of Wonosobo, with its abundant carica, opens up opportunities for developing high-value products that can boost the local economy. Carica contains essential nutrients such as vitamin C, vitamin B1, carotene, calcium, phosphorus, iron, and high fiber with low calories, making it ideal for healthy snacks. Innovative carica candy products based on stevia as a natural, calorie-free sweetener are being developed to meet consumer demand for healthy foods that are suitable for diabetics and individuals on a low-sugar diet. The combination of the nutritional advantages of carica fruit and the natural sweetness of stevia produces a low-calorie, high-fiber product free from synthetic ingredients. Market interest surveys show high enthusiasm from various community segments for this product, indicating broad market potential from local to national and international levels. Analysis shows a production breakeven point of 300 packages per month with a revenue-to-cost ratio of 1.15, indicating that this business is viable and capable of generating significant profits. Digital marketing strategies and collaboration with SMEs are key to expanding distribution and enhancing the added value of local products.